2010
DOI: 10.1016/j.ymeth.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of messenger RNA expression by in situ hybridization using RNA probes synthesized via in vitro transcription

Abstract: The analysis of the spatial patterning of mRNA expression is critically important for assigning functional and physiological significance to a given gene product. Given the tens of thousands of mRNAs in the mammalian genome, a full assessment of individual gene functions would ideally be overlaid upon knowledge of the specific cell types expressing each mRNA. In situ hybridization approaches represent a molecular biological/histological method that can reveal cellular patterns of mRNA expression. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
0
12
0
5
Order By: Relevance
“…Probes were purified using BioRad P-6 columns; the effluent was measured with a scintillation counter and then diluted with hybridization solution (~2 × 10 6 cpms of probe in 40 μl hybridization buffer per slide). All remaining tissue processing steps were performed according to published lab protocols (Carter et al, 2010). Probe hybridization specificity was defined in control experiments by sense probes which failed to yield autoradiographic signals above background.…”
Section: Methodsmentioning
confidence: 99%
“…Probes were purified using BioRad P-6 columns; the effluent was measured with a scintillation counter and then diluted with hybridization solution (~2 × 10 6 cpms of probe in 40 μl hybridization buffer per slide). All remaining tissue processing steps were performed according to published lab protocols (Carter et al, 2010). Probe hybridization specificity was defined in control experiments by sense probes which failed to yield autoradiographic signals above background.…”
Section: Methodsmentioning
confidence: 99%
“…Applications are very diverse including the analysis of gene expression; the study of molecular mechanisms implicated in certain diseases; or the detection of pathogenic agents [15][16][17]. Those application for the detection of fungus or bacteria are usually based on fluorescence (FISH), by using fluorochromes as reporter molecules [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, enzyme activity can be quickly distinguished by placing the tissue in the dry ice/alcohol solution 5,12 . Although quick preservation is critical for hybridization using a riboprobe 13 , little is known about experimental conditions for oligonucleotide probes. In this study using oligonucleotide probes, we found that there was no difference between the paraformaldehyde-prefixed and fresh brains quickly preserved in the ice/alcohol solution.…”
Section: Discussionmentioning
confidence: 99%